A Workshop on Basic Statistics With The R Programming Language at SMA Erenos Tangerang - Valensius Jimy; Dhela Asafiani Agatha; Ferdinand Nathaniel Widjaya; Bakti Siregar (CV. Syntax Corporation Indonesia, 2023)
The goal of the article is to find out and interpret the effect of giving a workshop on basic statistics with the R Programming Language at SMA ERENOS Tangerang. Researchers used descriptive statistics and basic inferential statistics to analyse student performances. The sample was taken as seventy-two students from SMA Erenos, where the actual number of students was ninety-six for grades X and XI majoring in science and social studies. The score of students was carried out directly from the Quizziz website and it is divided into two sessions, namely the Pre-Test and Post-Test. The results of this study obtained a real influence on learning basic statistics before and after the workshop. Therefore it can be concluded that when students have been given the right method to learn statistics or any other subject, it would be increased the performance of the students.